2013
DOI: 10.1177/0969733012466002
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurses’ perception of futility

Abstract: Suffering repeated experiences of moral distress in intensive care units due to applications of futility reflects on nurses' patient care negatively, increases their burnout, and reduces their job satisfaction. This study was carried out to investigate the levels of job satisfaction and exhaustion suffered by intensive care nurses and the relationship between them through the futility dimension of the issue. The study included 138 intensive care nurses. The data were obtained with the futility questionnaire de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 35 publications
4
23
0
4
Order By: Relevance
“…[25][26][27] Role definitions also provide information about expected and desired attributes such as educational qualifications, competencies and responsibilities, and reporting lines. [22] Establishing consensus about role definitions and responsibilities is necessary to optimise role enactment, maintain job satisfaction, [28] attract nurses to the speciality and inform peers and other professionals understanding of role expectations. [4] …”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Role definitions also provide information about expected and desired attributes such as educational qualifications, competencies and responsibilities, and reporting lines. [22] Establishing consensus about role definitions and responsibilities is necessary to optimise role enactment, maintain job satisfaction, [28] attract nurses to the speciality and inform peers and other professionals understanding of role expectations. [4] …”
Section: Discussionmentioning
confidence: 99%
“…1 Son zamanlarda sağlık çalışanlarının, adli vakalarla daha çok karşılaşma oranlarının artması nedeni ile sağlık uygulamalarında adli boyut daha fazla ön plana çıkmakta ve önemi her geçen gün giderek artmaktadır. 2 Aile içi şiddet, cinsel saldırı ve istismar gibi olayların yanı sıra her türlü kazalar ve yaralanmalarda da sağlık çalışanları görev almaktadır. İntihar girişimleri, alkol ve madde bağımlılığı, ilaç ve gıda zehirlenmeleri ve malpraktis gibi birçok adli vakalara da sağlık çalışanları tedavi ve bakım hizmeti sağlamaktadır.…”
unclassified
“…Ayrıca kanıtın tanımlanması, derlenip toplanması, muhafaza edilmesi, koruma zincirinin sağlanması, kayıt altına alınması ve krize müdahale gibi bileşenleri de bulunmaktadır. 2 Adli vakanın saptanabilmesi, kanıtların tanımlanıp toplanması, muhafaza edilmesi ve kayıt altına alınması için hemşirelerin yeterli bilgi ve beceriye sahip olması, ayrıca buna yönelik olarak uygun yaklaşımda bulunabilmesi oldukça önemlidir. Ek olarak, adli ekipte meydana gelen birçok adli olayın çözümünde adli tıp konusunda eğitim almış adli hemşirelerin katkısı yatsın-mamalıdır.…”
unclassified
“…Th is study fi ndings also defi ned other stressors associated with burnout such as resource inadequacy and security risks, but did not fi nd decision-making process to be crucial for decreased job satisfaction 11 . Ozden et al 12 identifi ed futility of care as a factor aff ecting job satisfaction and burnout experienced by nurses working in intensive care units. Th is paper gives a new perspective related to the futility dimension in nursing care and raising awareness among health professionals 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Ozden et al 12 identifi ed futility of care as a factor aff ecting job satisfaction and burnout experienced by nurses working in intensive care units. Th is paper gives a new perspective related to the futility dimension in nursing care and raising awareness among health professionals 12 . Th e study by Panunto et al showed that nurses with greater autonomy experienced lower levels of emotional exhaustion, which was refl ected in lower intention to leave their job, greater job satisfaction, and the perception of improved quality of care 13 .…”
Section: Discussionmentioning
confidence: 99%